Fintech : the new DNA of financial services - Gupta, Pranay, 1966-; Tham, T. Mandy (Walter de Gruyter Inc., 2019)
"This extraordinary book, written by leading players in a burgeoning technology revolution, is about the merger of finance and technology (fintech), and covers its various aspects and how they impact each discipline within the financial services industry. It is an honest and direct analysis of where each segment of financial services will stand. Fintech: The New DNA of Financial Services provides an in-depth introduction to understanding the various areas of fintech and terminology such as AI, big data, robo-advisory, blockchain, cryptocurrency, InsurTech, cloud computing, crowdfunding and many more. Contributions from fintech innovators discuss banking, insurance and investment management applications, as well as the legal and human resource implications of fintech in the future."- Resumé vydavatel
Keywords: finanční služby; inovace; financial services industry; innovations; elektronické knihy; monografie; electronic books; monographs